DAMPAK KEBIJAKAN PEMBATASAN IMPOR BAWANG MERAH TERHADAP USAHA TANIBAWANG MERAH DI KABUPATEN PROBOLINGGO - , Mohammad Wahyudin ([Yogyakarta] : Universitas Gadjah Mada, 2014)
On January - August 2013, the government implemented a quota-based import restriction policy for the shallot. While on September 2013, the government then changed it into a price-based import restriction. This research aims to determine how the impact of the quota-based and price-based import restrictions to the level of protection, profitability, and efficiency of farm. This research also aims to find alternative policies to increase the protection and profitability of farm. The method of analysis used in this research is PAM (Policy Analysis Matrix) method. The results showed that protection, profitability, and efficiency of farm increased 159%, 277%, and 57% after the policy of quota-based import restriction. While protection and profitability of farm decreased 28% and 64%, and efficiency of farm increased 1,7% after the policy of price-based import restriction. Meanwhile, farmers neededimprovement of seeds quality, provision of fertilizer subsidies based on farmersâ needs, implementation of the minimum price of shallots at the farm level, and provision of information services for the price of shallots to increase the protection and profitability of farm.